Digital Literacy in Madrasah Curriculum: Preparing Students for the Global Digital Economy - Luthfiah (Islamic Journal of Teaching and Learning, 2025)
Digital literacy is an essential skill in today's global era, especially to prepare students for the challenges of the digital economy. This study identifies the urgent need to integrate digital literacy in the madrasah curriculum in Indonesia to improve students' skills in the critical and responsible use of technology. This study uses a qualitative approach with a case study design, which involves interviews, observations, and document analysis. The results show that many teachers and students in madrassas have a basic understanding of digital literacy, but limitations in technology infrastructure and teacher training are significant obstacles to effective implementation. With the comprehensive integration of digital literacy, the madrasah curriculum is expected to be able to equip students with digital skills that are relevant to the needs of the global job market. The study recommends the development of ongoing teacher training as well as curriculum updates to include critical digital skills and cybersecurity.